Analysis on the Application of Communicative Language Teaching in Senior High School English Class - Chu, Xiaojiao (Journal of Theory and Practice of Contemporary Education, 2023)
Communicative Language Teaching method is one of the main teaching methods in foreign language teaching. According to CLT, the foreign language classroom should be a place which is full of communication, and the final destination of English learning is communication. Compared with traditional teaching methods, communicative teaching method has its unique charm and characteristics. English is a language. The purpose of English teaching is to let students learn to communicate in English. As language becomes a means of communication, the acquisition of foreign language knowledge and communicative competence depends on specific communicative activities such as listening, speaking, reading and writing. The English syllabus also clearly requires that English teaching should cultivate students' communicative competence. However, looking at the current situation of English Teaching in China, it can be found that the vast majority of students' ability to communicate in English is relatively weak. In order to improve students' ability to communicate in English, communicative teaching method has been paid more and more attention by teachers. However, it is undeniable that everything has two sides. There are also many deficiencies in the implementation of communicative teaching method, which need us to further explore. Therefore, this thesis focuses on the evaluation and analysis of the application of Communicative Language Teaching of teaching practice.